Comparison of olanexidine versus povidone-iodine for preventing surgical site infection in gastrointestinal surgery: study protocol for a multicentre, single-blind, randomised controlled clinical trial. Issue 5 (28th May 2019) - Takeuchi, Masashi; Obara, Hideaki; Kawakubo, Hirofumi; Shinoda, Masahiro; Okabayashi, Koji; Mayanagi, Shuhei; Irino, Tomoyuki; Fukuda, Kazumasa; Nakamura, Rieko; Wada, Norihito; Kitago, Minoru; Yagi, Hiroshi; et al.
Abstract : Introduction: The prevalence of surgical site infection (SSI) remains higher in gastrointestinal surgery than in other surgeries. Although several guidelines have indicated the efficacy of chlorhexidine and povidone-iodine in reducing the SSI rate, the optimal recommendation has still not been established. Therefore, it is necessary to determine the more effective antiseptic for surgical site preparation. Olanexidine (1.5% olanedine, Otsuka Pharmaceutical Factory, Tokushima, Japan), which is a new antiseptic in Japan, has antimicrobial activity against a wide range of bacteria, including Gram-positive and Gram-negative bacteria. Our study will contribute to determining a new antiseptic for use in gastrointestinal and other surgeries. Methods and analysis: We propose a multicentre, randomised controlled clinical trial for comparing two treatments, that is, 1.5% olanexidine or 10% povidone-iodine, for surgical skin preparation to prevent SSI in clean-contaminated gastrointestinal surgeries with surgical wounds. Patients aged ≥20 years at the time of consent will be included. The primary outcome measure is the 30-day postoperative SSI rate. For the primary analysis, which is aimed at comparing the treatment effects, the adjusted risk ratio and its 95% CI will be estimated using the Mantel-Haenszel method. Ethics and dissemination: The protocol was first approved by the Institutional Review Board of Keio University School of Medicine, followed by the institutional review board of each participating site. Participant recruitment began in June 2018. The final results will be published in international peer-reviewed medical journals. Trial registration number: UMIN 000031560; Pre-results.